2020
DOI: 10.1111/cas.14745
|View full text |Cite
|
Sign up to set email alerts
|

Multigene model for predicting metastatic prostate cancer using circulating tumor cells by microfluidic magnetophoresis

Abstract: We aimed to isolate circulating tumor cells (CTCs) using a microfluidic technique with a novel lateral magnetophoretic microseparator. Prostate cancer–specific gene expressions were evaluated using mRNA from the isolated CTCs. A CTC‐based multigene model was then developed for identifying advanced prostate cancer. Peripheral blood samples were obtained from five healthy donors and patients with localized prostate cancer (26 cases), metastatic hormone‐sensitive prostate cancer (mHSPC, 10 cases), and metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…As mentioned previously, CTCs in the bloodstream can be classified into three types, and their detection relied on a combination of membrane filtration and epithelial/mesenchymal biomarker-based identification. Recent reports indicated that the expression of EMT markers in CTCs is relevant process for invasion and metastasis in several cancers, such as breast, colorectal, nonsmall cell lung, gastric, and prostate cancers [ 26 30 ]. The CTC detection method in the present study allowed the isolation of pivotal EMT CTCs in renal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, CTCs in the bloodstream can be classified into three types, and their detection relied on a combination of membrane filtration and epithelial/mesenchymal biomarker-based identification. Recent reports indicated that the expression of EMT markers in CTCs is relevant process for invasion and metastasis in several cancers, such as breast, colorectal, nonsmall cell lung, gastric, and prostate cancers [ 26 30 ]. The CTC detection method in the present study allowed the isolation of pivotal EMT CTCs in renal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CTC positivity for the examined patient cohort was defined as the expression of at least 1 of the following 12 biomarkers: AR-V7, AKR1C3, AKT2, ALDH1, AR, EPCAM, PSMA, MDK, PIK3CA, PSCA, TUBB3, VIM. These biomarkers were selected based on literature data supporting their capacity to identify CTC as positive in prostate cancer or confirming their role in prostate cancer or in EMT [ 28 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the discovery that androgen receptor (AR)-targeting agents are closely related to the AR splice variant expressed on CTCs in advanced prostate cancer, CTC-based genomic analysis has been highlighted. 11 , 12 , 13 However, genomic analysis of CTCs remains challenging despite the development of novel techniques such as next-generation sequencing and droplet digital PCR (ddPCR) because of the presence of trace amounts of CTCs in blood. Recently, technology capable of separating CTCs more effectively has been developed and can be used for identifying biomarkers in PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, technology capable of separating CTCs more effectively has been developed and can be used for identifying biomarkers in PCa. 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation